Enhanced resolution of a surface plasmon resonance sensor detecting C-reactive protein via a bimetallic waveguide-coupled mode approach - Lee, Hwa-Seub; Seong, Tae-Yeon; Kim, Won Mok; Kim, Inho; Hwang, Gyu-Weon; Lee, Wook Seong; Lee, Kyeong-Seok (ELSEVIER SCIENCE SA, 2018)
Extensive efforts have been devoted to improving the resolution of surface plasmon resonance (SPR) sensors in the detection of trace levels of biomolecules considered essential for the early diagnosis of disease. As part of these efforts, we previously developed a bimetallic waveguide-coupled surface plasmon resonance (Bi-WCSPR) sensor configuration designed to dramatically reduce the linewidth of the SPR curve while preserving a moderate local field decay length, thereby addressing the resolution issue. In this study, we systematically quantified the enhanced resolution in Bi-WCSPR sensors used to detect C-reactive protein (CRP), a widely accepted biomarker of inflammation in cardiovascular disease. Individual SPR sensorgrams were measured at several CRP concentrations in both the intensity and angular interrogation modes, confirming that the Bi-WCSPR configuration with a high Ag-to-Au ratio provided a figure-of-merit (FOM) that was 2.53 times higher than that of conventional Au sensors and a limit-of-detection (LOD) that was an order of magnitude lower than the cut-off level for CRP. It was found that when using the Bi-WCSPR configurations, the resolution enhancement in the intensity interrogation mode becomes more evident as the CRP concentrations is lowered to the cut-off level. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: FIELD-EFFECT-TRANSISTOR; UNSTABLE ANGINA; SENSITIVITY; BIOSENSORS; RANGE; IMMUNOSENSOR; LAYERS; FILM; VARIANTS; EVENTS